2019
DOI: 10.3889/oamjms.2019.534
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Anti-Oxidant Markers in Premature Infants with Respiratory Distress Syndrome

Abstract: BACKGROUND:Neonatal respiratory distress syndrome (RDS) caused by decreased surfactant and structural lung immaturity. The imbalance between oxidative status and antioxidant defence system was suggested to be an important trigger for lung affection with RDS.AIM:The goal of the current research was to elucidate the significance of the oxidant/ antioxidant status in the pathogenesis of RDS in preterm infants.PATIENTS AND METHODS:This controlled study included 31 preterm neonates with RDS and 36 healthy preterm n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In agreement with our results, some studies indicated that the increased OS accompanied by reduced antioxidant defenses may play a significant role in the pathogenesis of RD in preterm newborns 67 and our results agreed with some studies revealed that there was an evidence of oxidative damage and diminished antioxidant defenses in newborns with RDS and the neonatal RDS is associated with certain damage of the cell lipids, proteins and DNA, due to the effect of oxidative stress. 68 …”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results, some studies indicated that the increased OS accompanied by reduced antioxidant defenses may play a significant role in the pathogenesis of RD in preterm newborns 67 and our results agreed with some studies revealed that there was an evidence of oxidative damage and diminished antioxidant defenses in newborns with RDS and the neonatal RDS is associated with certain damage of the cell lipids, proteins and DNA, due to the effect of oxidative stress. 68 …”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, birth weight and gestational age were negatively correlated with both plasma protein carbonyls and oxidant/antioxidants ratio, whereas non-significant correlations were found between the levels of OS markers and the severity of RDS ( 35 ). The role of OS in neonatal lung injury has been confirmed in a study showing a significant increase of MDA and H 2 O 2 plasma levels ( p < 0.005) in preterms with RDS (mean GA 31.2 ± 3.2 weeks) in comparison with healthy controls ( 36 ). Recently, Elkabany et al ( 37 ) demonstrated that serum birth levels of MDA, AOPPs, and 8-OHdG were significantly higher ( p = 0.031, p < 0.001, p < 0.001, respectively) in newborns with RDS than controls, with a further increase after 3 days ( p < 0.001).…”
Section: Oxidative Stress and Neonatal Lung Diseasementioning
confidence: 77%
“…Respiratory distress syndrome (RDS), formerly known as hyaline membrane disease, is a disease of premature infants characterized by structural immaturity of peripheral airways and surfactant deficiency [18]. Male infants are more significantly affected by RDS than girls [24]. Male predisposition appears to be due to the inhibitory effect of androgens on lung maturation and surfactant production [25].…”
Section: Oxidative Stress and Respiratory Distress Syndromementioning
confidence: 99%
“…Dizdar et al demonstrated that in children with RDS, the increase in oxidant status against antioxidant mechanisms is associated in a proportional manner with greater severity and mortality [28]. Extremely premature and very low birth weight infants are more susceptible to rapid formation of free radicals, and therefore to RDS [24]. ROS lead to an increase in the permeability of the endothelium, resulting in the passage of polymorphonuclear leukocytes (PMNs) into the alveolar lumen and the release of cytokines, free radicals, and toxic nitrogen derivatives (RNS) that amplify the inflammatory process [18,29].…”
Section: Oxidative Stress and Respiratory Distress Syndromementioning
confidence: 99%